Interjection by commentators in identity V E-Sports tournament - Surjadi, Edgina Vivien; Aryanto, Bayu (Japanese Research on Linguistics, Literature, and Culture, 2022)
The aim of this research is to describe the functions of interjections spoken by two commentators called jikkyousha and kaisetsusha in Identity V e-sports tournament with a pragmatic approach. A qualitative descriptive method was used in this research. Interjections were analyzed using Namatame Yasu and Masuoka-Takubo’s interjection theory. The results show 12 functions of interjections: facing a new situation, expressing deep feelings for something, politely affirming what interlocutors said, agreeing, disagreeing, approval, attention, surprise, recalled, expressions of thought, taking back what the speaker said, and greeting. Expression of facing a new situation is the most spoken interjection.